2015
DOI: 10.1021/acs.jctc.5b00083
|View full text |Cite
|
Sign up to set email alerts
|

Components of the Bond Energy in Polar Diatomic Molecules, Radicals, and Ions Formed by Group-1 and Group-2 Metal Atoms

Abstract: Although many transition metal complexes are known to have high multireference character, the multireference character of main-group closed-shell singlet diatomic molecules like BeF, CaO, and MgO has been less studied. However, many group-1 and group-2 diatomic molecules do have multireference character, and they provide informative systems for studying multireference character because they are simpler than transition metal compounds. The goal of the present work is to understand these multireference systems b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 87 publications
1
30
0
Order By: Relevance
“…For instance, Truhlar and Yu showed that CaO, MgO, and MgS, despite being in a singlet state, have multireference character. [50] Similarly, Badri et al have reviewed the ring current model in all-metal clusters and they found that in the Sc 2 3 cluster a multireference study is necessary. [51] Conversely, the MICD module in DIRAC is not programmed to treat multireference ground states and, therefore, the present study utilized the same approach as for the other molecules.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Truhlar and Yu showed that CaO, MgO, and MgS, despite being in a singlet state, have multireference character. [50] Similarly, Badri et al have reviewed the ring current model in all-metal clusters and they found that in the Sc 2 3 cluster a multireference study is necessary. [51] Conversely, the MICD module in DIRAC is not programmed to treat multireference ground states and, therefore, the present study utilized the same approach as for the other molecules.…”
Section: Resultsmentioning
confidence: 99%
“…23 However, closer analysis shows that ''pure'' one-electron SIEeffects are hard to capture with this set, and therefore we herein ) for which their dissociation energies at four different points along their dissociation potential energy curves are calculated: at their respective inter-monomeric equilibrium distance, 1.25 times, 1.5 times and 1.75 times their equilibrium distance. The relevant structures were optimised at the SCS-MP2 117 /def2-TZVPP level 59 We adopted ten of those dimers from their study to form the new ALKBDE10 test set: BeF, BeO, CaO, HF, KF, LiF, KF, LiF, LiO, MgO, MgS, and NaO. All structures are based on the PW6B95-D3(BJ)/def2-QZVPP level of theory.…”
Section: 14mentioning
confidence: 99%
“…For more details of all the subsets of every database, as well as references to their original sources, and a better overview of their overlaps, see also the Supporting Information …”
Section: Structure Of the Databasementioning
confidence: 99%